Design and Validation of a Scale to Assess Dairy Farmers’ Attitudes toward Climate-Resilient Dairy Farming - ALI, WARIS; MAJI, SAIKAT; Roy, Suman; Srivastava, Shalu; M, CHENNAMADHAVA (Indian Journal of Extension Education, 2025)
The study, carried out in 2025, aimed to develop a tool for assessing dairy farmers’ attitudes toward climate-resilient dairy farming practices. For this purpose, an attitude scale was created using a Likert-type scale development method. Initially, 50 statements were compiled (both positive and negative) together and later improved in accordance with Edward’s fourteen principles for constructing scales. The overall mean relevancy score obtained was 3.191. In a non-sampling area, a pilot study involving 60 farmers was undertaken, after which 27 statements were kept for subsequent analysis. Subsequently, after calculating the t-values for all statements, 23 had t-values of 1.75 or higher. A Cronbach’s alpha of 0.732 indicated the scale’s internal consistency, and the scale’s content validity was determined based on the experts’ evaluation. This completed scale is suitable for measuring the attitude of dairy farmers toward climate-responsive dairy practices in the current research setting, and with proper contextual adjustments, it can be used in other regions as well.